”Vi har lært at blive små sammen omkring de store spørgsmål.”: Hvordan forske i eksistentiel og åndelig omsorg, når fokus er på den filosofiske samtaledimension i palliativt arbejde? - Hansen, Finn Thorbjørn (Academic Quarter | Akademisk kvarter, 2015)
This article describes a ‘third way’ to a work with spiritual care in palliation. Normally spiritual care is theoretically understood and practically unfolded through either a psychological (therapeutic) or theological (pastoral counselling) approach. In a 3-year action research project on a Danish hospice the action researcher and the ‘actors’ or co-inquirers from the hospice had a shared inquiry into how philosophical conversations may be another way to strengthen a palliative team’s qualifications to lead conversations with patients, relatives and other colleagues about the Big Question of Life and Death. The article focus on the special kind of Socratic and phenomenological action research that is needed compare to other more empirical-descriptive research approaches when we are working with existential, ethical and spiritual experiences.